Safety Issue Associated With Hotwork on Conveyor Belt Area of Self-Unloading Bulk Carrier - Hendra Saputra; Mufti Fathonah Muvariz; Nidia Yuniarsih; Nauval Abdurahman; Sapto Wiratno Satoto; Rifel Landong (Politeknik Negeri Batam, 2015)
Welding, cutting, burning, abrasive blasting, and other heat-producing operations are considered as hotwork that potentially creates fire hazard especially on board a ship. Fires in confined spaces such ship compartments, in the loop and tunnel areas are very dangerous, as the conditions are conducive to its rapid spread and also that they are in the vicinity of highly flammable areas. When hot work is being performed in the areas and spaces, required standards and procedures are essential to ensure the safety of all involved in the work. This study try to review some causes of ship fire accident that took place in the past and came out with suggestions for improvement in the area of hotworks in close proximity to a conveyor belt. On methodology, using a case study of an accident on board a ship to know cause that often occur around conveyor belt area of Self-Unloading Carrier (SUL) especially on bulk carrier. The result of study is to reiterate the need for proper monitoring and and supervision of hotwork in close proximity to a conveyor belt as it has contributed adversely to the several fire accident that has taken place in the world shipping trade most especially on the self-unloading(SUL) bulk carriers.